Structural dynamics and membrane interaction of the chloride intracellular channel protein, CLIC1 - Nathaniel, Christos (My University, 2008)
ABSTRACT The Chloride Intracellular Channel (CLIC) proteins are a family of amphitropic proteins that can convert from soluble to integral membrane forms. CLIC1 is a member of this family that functions as a chloride channel in the plasma and nuclear membranes of cells. Although high-resolution structural data exists for the soluble form of monomeric CLIC1, not much is known about the integral membrane forms’ structure. The exact mechanism and signals involved in the conversion of the soluble form to membrane-inserted form are also not clear. Studies were undertaken in the absence and presence of membrane models. Analysis of the structure and stability of CLIC1 in the absence of membrane investigated the effect of possible signals or triggers that may play a crucial role in the conversion of the soluble form to integral membrane form. Exposing CLIC1 to oxidizing conditions results in the formation of a dimeric form. The CLIC1 dimer was found to be less stable than the monomeric form based on unfolding kinetic studies. The stability of the dimer was also less influenced by salt concentration, compared with the monomer. The effect of pH on the structure of CLIC1 is of physiological relevance since the movement of soluble CLIC1 in the cytoplasm or nucleoplasm toward the membrane will involve the protein being exposed to a lower pH micro-environment. Hydrogen exchange mass spectrometry was used to study the structural dynamics of CLIC1 at pH 7.0 and pH 5.5. At neutral pH, domain II is more stable than the more flexible thioredoxin domain I. The thioredoxin-fold therefore is more likely to unfold and rearrange to insert into membranes. Because of the high stability of domain II this region is probably where the folding nucleus of the protein is. At pH 5.5 it was found that the a1, a3 and a6 helices, which are spatially adjacent to one another across the domain interface, were destabilized. This destabilization may be the trigger for CLIC1 to unfold and rearrange into a membrane insertion-competent form. The role of the primary sequence and unique three-dimensional structure of CLIC1 in membrane insertion was investigated in a bioinformatics-based study that looked at conserved residue features such as hydropathy and charge. Hidden helical propensities and Ncapping motifs in the a1-b2 region were found, which may have important implications for locating putative transmembrane regions. Analysis of the structure and thermodynamics of CLIC1 interacting with membranes investigated changes in secondary structure, tertiary structure, hydrodynamic volume and thermodynamics when CLIC1 is exposed to membrane-mimicking models. The effect of a variety of conditions such as pH and redox, cysteine-modifiying agents (NEM), ligands (GSH), and inhibitors (IAA) on CLIC1 membrane interaction were studied. It was found that CLIC1 interacted with membranes more favourably at lower pH and that NEM completely inhibited CLIC1 interaction with micelles.
Keywords: membrane insertion; amphitropic; ion channel; pore